Longitudinal Control Strategy Investigation for Coaxial Compound Helicopters - Ye Yuan (75th Annual Vertical Flight Society Forum and Technology Display (FORUM 75): The Future of Vertical Flight, 2019)
The coaxial compound helicopters have obtained a lot of research interest due to their outstanding performance, especially in high speed flight. This rotorcraft could use the longitudinal cyclic pitch and the elevator to control the pitching moment during the flight. In order to investigate the effect of different longitudinal control strategy on the flight dynamics characteristics of this helicopter, a validated flight dynamics model is utilized to calculate the control derivatives, the bandwidth and phase delay, the attitude quickness, and the control inputs and pilot workload during the Pull-up & Push-over manoeuvre. The results indicate that control power of the longitudinal cyclic pitch is higher than that of the elevator, especially in hover and low speed forward flight due to the lack of the dynamic pressure on the elevator. The bandwidth and phase delay results demonstrate that both longitudinal control strategy could attain satisfactory small-amplitude response characteristics, and the attitude quickness results show that the helicopter capability in moderate to large control response is relatively high due to the additional damping provided by the rigid rotor. The manoeuvre simulation results indicate that using reasonable allocation between the longitudinal cyclic pitch and elevator is an efficient method to reduce the pilot workload and the maximum power consumption during manoeuvring flight.